Effects of microgravity on osteoblast mitochondria: a proteomic and metabolomics profile. Issue 1 (December 2017) - Michaletti, Anna; Gioia, Magda; Tarantino, Umberto; Zolla, Lello
Abstract The response of human primary osteoblasts exposed to simulated microgravity has been investigated and analysis of metabolomic and proteomic profiles demonstrated a prominent dysregulation of mitochondrion homeostasis. Gravitational unloading treatment induced a decrease in mitochondrial proteins, mainly affecting efficiency of the respiratory chain. Metabolomic analysis revealed that microgravity influenced several metabolic pathways; stimulating glycolysis and the pentose phosphate pathways, while the Krebs cycle was interrupted at succinate-fumarate transformation. Interestingly, proteomic analysis revealed that Complex II of the mitochondrial respiratory chain, which catalyses the biotransformation of this step, was under-represented by 50%. Accordingly, down-regulation of quinones 9 and 10 was measured. Complex III resulted in up-regulation by 60%, while Complex IV was down-regulated by 14%, accompanied by a reduction in proton transport synthesis of ATP. Finally, microgravity treatment induced an oxidative stress response, indicated by significant decreases in oxidised glutathione and antioxidant enzymes. Decrease in malate dehydrogenase induced a reverse in the malate-aspartate shuttle, contributing to dysregulation of ATP synthesis. Beta-oxidation of fatty acids was inhibited, promoting triglyceride production along with a reduction in the glycerol shuttle. Taken together, our findings suggest that microgravity may suppress bone cell functions, impairing mitochondrial energy potential and the energy state of the cell.